2017
DOI: 10.1007/s40263-017-0484-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Combined Pharmacotherapy for the Treatment of Alcohol Use Disorder in Patients Without Comorbid Conditions

Abstract: No significant benefit for the use of combinations over single agents was observed. However, benefit may be observed when combined pharmacological interventions address specific symptoms of alcohol use disorder known to be influenced by combination components, or when combinations are used in specific subpopulations in which combination components demonstrate benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The current findings also suggest the potential importance of modeling within‐person variability in medication adherence. Given efforts to augment naltrexone with other pharmacotherapies (Naglich et al, ), incorporating these approaches in studies of combined pharmacotherapies is another potential direction. Overall, precision medicine studies—and pharmacotherapy trials more broadly—might benefit from more frequent incorporation of high‐density assessments in order to model behavior change and clinical outcomes with greater temporal precision, allowing for process‐based investigations of treatment mechanisms and response.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings also suggest the potential importance of modeling within‐person variability in medication adherence. Given efforts to augment naltrexone with other pharmacotherapies (Naglich et al, ), incorporating these approaches in studies of combined pharmacotherapies is another potential direction. Overall, precision medicine studies—and pharmacotherapy trials more broadly—might benefit from more frequent incorporation of high‐density assessments in order to model behavior change and clinical outcomes with greater temporal precision, allowing for process‐based investigations of treatment mechanisms and response.…”
Section: Discussionmentioning
confidence: 99%
“…24 The limitation of scientific knowledge resulting from the present study and from personal experience is recognized beforehand, but the critical analyzes found in the articles allow us to conclude that of the four studies, three studies presented levels of evidence 1A and 1B. [16][17][18][19][20][21][22][23] Regarding the degree of recommendation, the level studies, on the one hand, present as a strong representation in the choice, excellent levels of evidence to recommend the conduct with Naltrexone, Acamprosate, and Disulfiram whose benefits have a weight greater than the gain, therefore they present conditions and recommendations for use. On the other hand, studies with level of recommendation B of level 1 refer to the generalization of the findings that can recommend the action in function of the important outcomes in relation to the risks of the damage, can be supported and recommended its use.…”
Section:  Naltrexone (Ntx)mentioning
confidence: 94%
“…In another with alcohol-dependent patients, found that individuals with a G allele had lower relapse rates with NTX, while those receiving placebo did not differ from other genotypes in terms of relapse. 23 In the last of the three trials conducted with individuals of European ancestry, the presence of a G allele was found to be associated with the reduced drink and increased abstinence in NTX, while subjects with an AA genotype showed no difference in response. A study with heavy drinkers showed that the ability of NTX to block alcoholinduced stimulation, positive mood, desire, and appreciation was greater in patients with the G allele.…”
Section:  Naltrexone (Ntx)mentioning
confidence: 99%
See 2 more Smart Citations